2009
DOI: 10.1186/1471-2431-9-69
|View full text |Cite
|
Sign up to set email alerts
|

Why do paediatricians prescribe antibiotics? Results of an Italian regional project

Abstract: Background: To investigate determinants of antibiotic prescription in paediatric care, as a first step of a multilevel intervention to improve prescribing for common respiratory tract infections (RTIs) in a northern Italian region with high antibiotic prescription rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 20 publications
7
87
3
1
Order By: Relevance
“…The prescribing attitudes of physicians with regards to acute otitis media (AOM) are in consistent with those reported in the international literature [13] [16]. In these studies, over 60% of pediatricians implemented the "watchful waiting" practice for the management of AOM, while other studies focusing on hospital and primary health care reported "watchful waiting" rates ranging from 45% to 50% [17] [18]. In addition, the often administration of antibiotics in pharyngitis without obtaining throat cultures is also reported by Geitona et al [13] and Paluck et al [18] As far as the use of antibiotics for the prevention of secondary respiratory tract infections, our study showed that it was slightly lower than those found in a Greek study [13].…”
Section: Discussionsupporting
confidence: 75%
“…The prescribing attitudes of physicians with regards to acute otitis media (AOM) are in consistent with those reported in the international literature [13] [16]. In these studies, over 60% of pediatricians implemented the "watchful waiting" practice for the management of AOM, while other studies focusing on hospital and primary health care reported "watchful waiting" rates ranging from 45% to 50% [17] [18]. In addition, the often administration of antibiotics in pharyngitis without obtaining throat cultures is also reported by Geitona et al [13] and Paluck et al [18] As far as the use of antibiotics for the prevention of secondary respiratory tract infections, our study showed that it was slightly lower than those found in a Greek study [13].…”
Section: Discussionsupporting
confidence: 75%
“…It is not surprising that in a study conducted in the outpatient setting, patients whose doctors routinely prescribed antibiotics for cold symptoms were more prone to use antibiotics without the advice of a physician (30). Finally, diagnostic uncertainty may also be addressed as a cause of inappropriate prescription (31). The findings in this study have important implications for understanding the targets of future educational campaigns to control the use and the misuse of antibiotics.…”
Section: Self-prescriptionmentioning
confidence: 81%
“…The parents' lack of knowledge about proper antibiotic use can, therefore, be expected to cause inappropriate antibiotic prescription. However, even when parents have a good understanding of the issue, physicians tend to prescribe antibiotics, because they perceive parents' queries about the treatment plan as an expectation for antibiotic use 50,53,54) . A previous study reported that parents were satisfied when the physicians took what they perceived as an adequate amount of time to examine their child, regardless of 0% 10% 20% 30% 40% 50% 60% 70% 80% 90% 100% more than 2 points whether an antibiotic was subsequently prescribed 57) .…”
Section: Can We Prescribe Fewer Antibiotics ?mentioning
confidence: 99%
“…Diagnostic uncertainty also results in inappropriate antibiotic use 54) . Currently, quick and easy devices for detecting antigens of etiological agents such as Mycoplasma, influenza virus, RSV, and adenovirus, are being developed.…”
Section: Can We Prescribe Fewer Antibiotics ?mentioning
confidence: 99%